Factors Affecting Consumer Interest in Shopping at Mangga 2 Traditional Market Surabaya - Adityawarman M Kouwagam; Yusril Asril Nasir; Arasy Alimudin (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The purpose of this study is to identify and analyze the factors that influence consumer interest in shopping at the Mangga 2 Traditional Market Surabaya. Design/methodology/approach: The research approach used in this study is a quantitative approach. In this study using a sample of 100 visitors who have done shopping at the Mangga 2 Traditional Market Surabaya. The technique used for sampling is by means of library research and field research such as observation and distributing questionnaires. The data analysis used is Multiple Linear Regression Analysis. Findings: 1) Price has a significant effect partially on Consumer Purchase Decisions at Mangga 2 Traditional Market Surabaya; 2) Place has a significant partial effect on Consumer Purchase Decisions at Mangga 2 Traditional Market Surabaya; 3) Product quality does not have a partial significant effect on Consumer Purchase Decisions at Mangga 2 Traditional Market Surabaya; 4) Service does not partially significantly affect Consumer Purchase Decisions at Mangga 2 Traditional Market Surabaya; 5) Facilities have a significant partial effect on Consumer Purchase Decisions at Mangga 2 Traditional Market Surabaya; 6) The variables of price (X1), place (X2), product quality (X3), service (X4), and facilities (X5) have a significant simultaneous effect on consumer purchasing decisions. The variables of price (X1), place (X2), and facilities (X5) have an effect on consumer purchasing decisions, while the variable quality of products (X3) and service (X4) has no effect on consumer purchasing decisions. Paper type: Research paper